Producción y mercados de la agroindustria azucarera del distrito de Cuernavaca, en la primera mitad del siglo XIX - Sánchez Santiró, Ernest (El Colegio de México, A.C., 2004)
This work describes the situation of the sugar agro-industry of the State of Mexico, established mainly in the district of Cuernavaca (Morelos), during the  first half of the nineteenth century.  The analysis is based on two main issues: commercial production of sugar haciendas and  their  markets. The  article  has the  double purpose of contributing to the  general discussion on Mexican economy  during the first half of the nineteenth century, and of determining a specific temporality for the development of sugar agro-industry during the whole century.